Sources and channels of nonlinearities and instabilities of the Phillips curve: Results for the euro area and its member states - Karsten Reichold; Martin Wagner; Milan Damjanović; Marija Drenkovska (Institut für Höhere Studien - Institute for Advanced Studies (IHS), 2022)
This paper presents evidence for sources and channels of nonlinearities and instabilities of the new Keynesian Phillips curve (NKPC) for the euro area and all but four member states over the last two decades prior to the COVID-19 crisis. The approach rests upon misspecification testing using auxiliary regressions based on the standard open-economy hybrid NKPC. Using a large number of specifications, this approach allows to systematically, i. e., based on a literature review, disentangle the evidence for nonlinearities and instabilities of the NKPC according to sources and channels. For the euro area and most considered member states, there is substantial evidence for nonlinearities and instabilities. The relatively most important channels of nonlinearities and instabilities are similar across countries, whereas the relatively most important sources differ across countries. The results strongly indicate the need for considering nonlinear NKPC relationships in empirical analyses and also point towards potentially useful nonlinear specifications.
Keywords: E31; E52; E58; F62; J11; 330; Euro area; instability; new Keynesian Phillips curve; nonlinearity; specification analysis